What Tests Are Useful to Investigate a Possible Infection of Total Ankle Arthroplasty (TAA)? What Are Their Thresholds?. (July 2019) - Uçkay, Ilker; Pedowitz, David; Assal, Mathieu; Stull, Justin D.
Recommendation: Overall, the approach to a potentially infected total ankle arthroplasty (TAA) does not change compared to other periprosthetic joint infections (PJIs). There are no novel or unique diagnostic procedures for TAA infection, specifically. Joint aspiration or intraoperative tissue/synovial biopsies with microbiological cultures are the most important diagnostic tests for suspected TAA infections. In the absence of specific data related to TAA, the threshold for these tests should be derived from the hip and knee PJI literature. Level of Evidence: Strong Delegate Vote: Agree: 100%, Disagree: 0%, Abstain: 0% (Unanimous, Strongest Consensus)